Kualitas Hidup Penderita Penyakit Hipertensi Peserta Prolanis Di Puskesmas Kecamatan Padang Utara Kota Padang - Abdiana Abdiana (Jurnal Sehat Mandiri, 2019)
Hypertension is the highest prevalence of visits every year. Data from the Health Office in Padang in 2013 showed that the visit of hypertension sufferers in 2013 was the highest visit with 6,714 new hypertension case visits and 35,054 old case visits. For this reason, it is necessary to conduct research in the context of maintaining health for BPJS Health participants who suffer from chronic diseases to achieve optimal quality of life, especially hypertension. The purpose of this study was to determine the quality of life of hypertension sufferers of Prolanis participants in Padang Utara District, Padang City. The study was conducted with a cross sectional design of hypertension disease prolanis participants in the district of Padang Utara, Padang City in 2017 as many as 126 people. The sampling technique is simple random sampling. Data were analyzed univariately and bivariately with Chi-square test. The results showed that most hypertension sufferers aged ≥60 years old, low educated, female sex, low education, married status and long suffered from hypertension <10 years. The conclusion of this study is that there is a significant relationship between marital status and the quality of life of hypertensive illnesses of prolanis participants in Padang Utara Subdistrict, Padang City. It is suggested that the Puskesmas formulate efforts to prevent hypertension and be a source of data for research organizations and other parties involved in preventing hypertension.